1993
DOI: 10.1093/infdis/167.3.675
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Hearing Loss in Experimental Pneumococcal Meningitis: Correlation with Cerebrospinal Fluid Cytochemistry

Abstract: The development of hearing loss and concomitant cerebrospinal fluid (CSF) cytochemical changes in a model of pneumococcal meningitis were examined. Rabbits were injected intracisternally with 10(5) pneumococci. Auditory evoked potentials to clicks and to 10- and 1-kHz tone bursts were recorded hourly; CSF was analyzed every 4 h. Sensorineural hearing loss developed in all animals beginning 12 h after infection and progressed to severe deafness. The onset of hearing loss was preceded by a CSF leukocytosis of > … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
45
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 32 publications
4
45
0
1
Order By: Relevance
“…Hearing loss was correlated with the level of CSF inflammation in a rabbit model of pneumococcal meningitis (40), and intrathecal administration of TNF-␣ alone was sufficient to induce cochlear injury similar to that observed with bacterial meningitis (15). Furthermore, TLR and MyD88 knockout mice demonstrated less hearing loss following pneumococcal meningitis (247).…”
Section: Cochlear Damage and Hearing Lossmentioning
confidence: 72%
See 1 more Smart Citation
“…Hearing loss was correlated with the level of CSF inflammation in a rabbit model of pneumococcal meningitis (40), and intrathecal administration of TNF-␣ alone was sufficient to induce cochlear injury similar to that observed with bacterial meningitis (15). Furthermore, TLR and MyD88 knockout mice demonstrated less hearing loss following pneumococcal meningitis (247).…”
Section: Cochlear Damage and Hearing Lossmentioning
confidence: 72%
“…The underlying pathophysiology has been studied in several animal models (39,40,45,244,421,477) Cochlear involvement may result from direct spread of pneumococcal infection from the meninges, CSF, and cochlear perilymphatic system (40,227,244). Alternatively, a hematogenous route may occur following bacteremia or sepsis (227,244).…”
Section: Cochlear Damage and Hearing Lossmentioning
confidence: 99%
“…Hearing loss results from involvement of the inner ear due to inflammation as pneumococci and leukocytes extend from the CSF to the perilymph via the cochlear aqueduct (4,5,11). In a model of pneumococcal meningitis the severity of permanent hearing impairment as assessed by the increase in the ABR thresholds 2 weeks after (20).…”
Section: Discussionmentioning
confidence: 99%
“…The role of cytokines and MMPs in the pathophysiology of the cochlear damage associated with pneumococcal meningitis is still unknown. However, it has been demonstrated that MMPs are constitutively expressed at high levels in the cochlea (8) and that in meningitis pneumococci and polymorphonuclear leukocytes (PMNs) extend from the cerebrospinal fluid (CSF) to the perilymph via the cochlear aqueduct (5).…”
mentioning
confidence: 99%
“…SNHL results from involvement of the inner ear due to inflammation as the cerebrospinal fluid (CSF) containing pneumococci and leukocytes extends from the subarachnoid space via the cochlear aqueduct to the perilymph (7)(8)(9). In an adult rat model of PM, the severity of permanent hearing impairment assessed 2 wk after the infection correlated significantly with the loss of type I spiral ganglion neurons (10).…”
mentioning
confidence: 99%